Educational Hybrids in Russian Higher Education - V. S. Senashenko; A. A. Makarova (Высшее образование в России)
The paper applies the conception of social hybridization as an instrument for scientific analysis of national educational reality. This work provides a  rationale of the hybrid nature of the national higher education system  modernization. The influence of integration preferences on the formation of  hybrid educational structures in the system of national higher education is  revealed. The hybrid system’s definition is given and the processes of  education sphere hybridization are considered. Various aspects of educational hybridization are discussed. In particular, the hybrid nature of the  competence approach is emphasized. The authors dwell on the features of  hybrid transformations in connection with educational reality and come to a  conclusion that today there is an artificial education system in Russia, which  generates the distorted educational forms distorting the Russian education  system due to a shift of educational activity meanings and the creation of  inverted structures. The paper considers the models of hybrid systems based  on converted forms. Inversion, like a virus, generates hybrids everywhere. The society and the basic social institutions have been  “hybridized” to a large extent. The realistic description of the arising hybrid  educational models requires bearing in mind the principle of additionality;  otherwise we will have a distorted idea about the transformations of  educational reality. We may observe this on the example of the forced  implementation of foreign educational models in domestic educational  environment. Hybrid educational systems should be “grown” but not  implanted.